Challenges of quality of work life: Evidence and implications in developed and developing countries - Beh, L.S. (2011)
In the promotion of health and well-being at work, recent evidence suggests that work can be good for health in reversing the harmful effects of unemployment but yet if one is unhappy in their working environment, one can easily fall into sickness absence or ill-health. This paper would deal with the well-being of the working age population deriving data and evidence and implications from surveys in specific industry and country. The nature and characteristics of the jobs, supportive colleagues and employers contribute in terms of satisfaction, reward, and improved performance. The concept of well-being is open to interpretation and cultural context in addition to changing perceptions of expectations in terms of work benefits and conditions given the presumption that there is relationship between good quality of work life and good health, in creating new perspectives on wealth and work, improving work and workplaces, and supporting people to work policies. This paper will contribute a critical perspective on the nexus between work and well being in developed and developing countries given the different contextual and cultural settings taking some evidence from empirical studies, reports to the governments, policies, etc., and there upon conceptual interpretation.